Notching Philanthropy: BUILDING SOCIAL CAPITAL revitalize NATIONS CRISIS IN THE MIDDLE OF MORAL NATION - I Ketut Margi (Jurnal Ilmiah Ilmu Sosial, 2016)
The Indonesian people are faced with a situation 'uncertainty moral' (indeterminancy of moral), a gray line of morality, one point of moral ambiguity, or the Indonesian nation was deep in the valley "horror mundi", or terrorized by 'rites of violence ", and further erosion of a sense of caring on themselves and the environment. Under these conditions there is a wide range of pressing questions to be answered, either in the form of thought and even if possible with real action. The question is why the question of which moral crisis that could occur and what can be contributed by the youth (student) to the bawdy-marutnya this nation? As agents of change, things you can do is to maintain and take care of social capital, in the form Bonding and Bridging by increasing trust towards abstract systems and the personal trust. Keywords: moral crisis, philanthropy, social capital, building a nation